Deficiencia de cinc en niños con desnutrición aguda grave (2005)
ABSTRACT: Zinc is one the most important trace elements, it is involved in a multitude of diverse catalityc, structural and regulatory functions in human cells. Zinc deficiency is asocciated with grow retardation, delayed sexual maturation, impaired taste, spina bifida malformation, and immune deficiencies that are related with some complications like diarrhea and neumonia. Plasma/ serum zinc concentrations has been designated as a measure of zinc body status, plasma zinc concentrations can be altered mainly in infection and malnutrition characterized by low albumin concentration, and fluid retention. Children with acute and severe malnutrition have zinc plasma concentrations below 50% compared with normal children. Because of zinc deficiency, malnourished children can not achieve the goals of the nutritional support. Furthemore, zinc suplementation may be considered as a nutritional therapy involved in the treatment of malnutrition.